2021
DOI: 10.3390/ijerph182413082
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Environmental Footprint through Employees: A Case of Female Leaders from the Perspective of CSR

Abstract: Environmental quality strongly depends on human behavior patterns. Many environmental challenges are rooted in human actions, and thus, it is believed that these problems can be reduced through the promotion of pro-environmental behaviors (PB). Owing to this reality, the current study aims to reduce the environmental footprint of a hospital by promoting its employees’ environment-specific behavior via corporate social responsibility (CSR) and ethical leadership (EL). More importantly, the study also considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 126 publications
2
5
0
Order By: Relevance
“…Finally, the result of multiple linear regression analysis indicated that different demographic variables have different effects on hospital workers’ CHRP, PEA, PEI, and PEB. Specifically, compared with males, females are more inclined to display more PEA and PEI, and then perform more PEB, which is consistent with the study of Swim, Gillis 146 , Ahmad, Ullah 23 , Singleton, Lau 17 , and Wei, Sial 141 . The social role theory-individuals incline to possess diverse roles and perform different behavior in the same social setting-can illustrate these differences between genders, females are more concerned about environmental issues and have a stronger willingness and belief to relieve or reverse them 23 , 141 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, the result of multiple linear regression analysis indicated that different demographic variables have different effects on hospital workers’ CHRP, PEA, PEI, and PEB. Specifically, compared with males, females are more inclined to display more PEA and PEI, and then perform more PEB, which is consistent with the study of Swim, Gillis 146 , Ahmad, Ullah 23 , Singleton, Lau 17 , and Wei, Sial 141 . The social role theory-individuals incline to possess diverse roles and perform different behavior in the same social setting-can illustrate these differences between genders, females are more concerned about environmental issues and have a stronger willingness and belief to relieve or reverse them 23 , 141 .…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, compared with males, females are more inclined to display more PEA and PEI, and then perform more PEB, which is consistent with the study of Swim, Gillis 146 , Ahmad, Ullah 23 , Singleton, Lau 17 , and Wei, Sial 141 . The social role theory-individuals incline to possess diverse roles and perform different behavior in the same social setting-can illustrate these differences between genders, females are more concerned about environmental issues and have a stronger willingness and belief to relieve or reverse them 23 , 141 . Therefore, the goal of mitigating and adapting to climate change can be a reality with the active participation of females.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pro-environmental behaviors denote people’s environmental behaviors toward sustainability [ 7 , 8 , 9 ]. However, previous studies have neglected how environmental social responsibility leads to pro-environmental behaviors; thus, firms have no idea how to formulate strategies that can induce employees’ pro-environmental behaviors [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, most research on employees in sustainability topics have been conducted in companies, for example, employees' proenvironmental behaviors [19], [20], [21], the role of employee commitment for green performance [22], the employees' attitude and performance [23], and the role of EP in the sustainability [24]. There is increasing, yet limited, research on other types of organizations [25], such as the effect of corporate social responsibility on job satisfaction and organizational commitment [26], green employee engagement in higher education organizations [27], and analyzing employees' green behavior in the public and private sectors [28].…”
Section: Introductionmentioning
confidence: 99%